Politicians and Pamphleteers: Propaganda During the English Civil Wars and Interregnum - Peacey, Jason (Taylor and Francis, 2017)
The English civil wars radically altered many aspects of mid-seventeenth century life, simultaneously creating a period of intense uncertainty and unheralded opportunity. Nowhere was this more apparent than in the printing and publishing industry, which between 1640 and 1660 produced a vast number of tracts and pamphlets on a bewildering variety of subjects. Many of these where of a highly political nature, the publication of which would have been unthinkable just a few years before. Whilst scholars have long recognised the importance of these publications, and have studied in depth what was written in them, much less work has been done on why they were produced. In this book Dr Peacey first highlights the different dynamics at work in the conception, publication and distribution of polemical works, and then pulls the strands together to study them against the wider political context. In so doing he provides a more complete understanding of the relationship between political events and literary and intellectual prose in an era of unrest and upheaval. By incorporating into the political history of the period some of the approaches utilized by scholars of book history, this study reveals the heightened importance of print in both the lives of members of the political nation and the minds of the political elite in the civil wars and Interregnum. Furthermore, it demonstrates both the existence and prevalence of print propaganda with which politicians became associated, and traces the processes by which it came to be produced, the means of detecting its existence, the ways in which politicians involved themselves in its production, the uses to which it was put, and the relationships between politicians and propagandists. Contents: Introduction; Part 1 The Motor of Propaganda: Politicians and the propaganda impulse; Authors and the propaganda impulse. Part 2 The Mechanics of Propaganda: Decoding pamphlets; Licensing and propaganda; Politicians and the press; Politicians and the writing process. Part 3 The Dynamics of Propaganda: The limits of propaganda; The propagandist and the politician. Epilogue: Propaganda, the state, and the public sphere; Bibliography; Index.